Characterizacion of bananas after application of different fungicide in post-harvest - Ferraz, Marcelo Vieira [UNESP]; Ferreira de Almeida, Luis Carlos [UNESP]; Silva, Lucas da [UNESP]; Santos Ribeiro de Amorim, Hernandes Damasceno [UNESP]; Chehoud Lemos Soares, Carlos Osorio [UNESP]; Ferraz, Marcos Vieira [UNESP]; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; Robinson, M. V.; RuizAltisent, M.; Ballesteros, F. R.; et al. (Fundacion General Univ Politecnica Madrid, 2014)
Little information exists about the postharvest behavior of bananas after application of fungicides in the Registro-SP region. This study aimed to evaluate the soluble solids (degrees Brix), pH, and total acidity of the bananas after the application of fungicides. The experimental design was completely randomized in a 4x2 fungicidal factorial with two concentrations for each fungicide and two degrees of maturity, plus additional treatment using only water, repeated in four seasons. Each experiment had three replications with four bouquets of five fruits. For acclimatized bananas, higher values of degrees Brix were observed in fruits treated with Propiconazole and Imidazole. For bananas not acclimatized minor degrees Brix values were observed for fruit treated with Azoxystrobin in autumn and lower pH values and higher acidity for bananas that were treated with Azoxystrobin in winter. We conclude that for acclimatized bananas, the products do not interfere with the quality of the fruit, regardless of their concentrations, in spring, summer and fall, because the values of degrees Brix, pH and acidity did not differ from the control. The same was observed for bananas not acclimatized in summer and winter.
Keywords: Post-harvest; ripening; quality; Musa ssp